Steel Design of Plated Structural Elements - A comparison of the effective width method and the reduced - Ahlstrand, Johan; Johansson, Ellen (My University, 2021)
There are two methods described in Eurocode 1993-1-5 that are used for capacity controls on members in cross-section class 4. The methods are called the effective width method and the reduced stress method. The aim of this thesis is to investigate if the capacity varies depending on which of the two methods is used and see in what design situation one or the other method provide a higher capacity. A parametric study of two box-beam sections is performed. The beams are a lon gitudinally stiffened box beam and an unstiffened box beam, where the height and width are kept constant as the thicknesses of the web and flange vary as well as the distance between transverse stiffeners. All variations of the two box beams are investigated with both methods from Eurocode 1993-1-5 and three different load ing combinations. The loading situations on the beams are either solely moment or shear force or a combination of both moment and shear force. An FE-analysis is performed to obtain the buckling mode which is used in the calculations of the reduced stress method. The results show that the reduced stress method is generally more conservative than the effective width method. However, there are a few geometric variations and loading situations where the reduced stress method results in a higher capacity. A low slenderness difference between flange and web yields a higher capacity for the reduced stress method and for an unstiffened beam and for a stiffened beam there are a lot of factors that impact the capacity when solely moment is considered. The lack of stress redistribution in the reduced stress method is a big disadvantage in order for it to result in the same capacity as the effective width method.
Keywords: Effective width method, Reduced stress method, Longitudinal stiffeners; Steel plates, Eurocode 1993-1-5, Finite Element Method